Marketing research of the domestic market of antibiotics and chemotherapeutic drugs for use in dermatology - T. P. Zarichna; T. S. Brytanova; T. S. Raikova (Zaporozhye State Medical University, 2022)
The aim of work is marketing research of the domestic market of antibiotics and chemotherapeutic drugs for use in dermatology. Materials and methods. To achieve this goal, electronic official sources of information and pharmacy websites were used. System-analytical, mathematical-statistical, and comparative methods of analysis were employed. Results. Analysis of the assortment structure of the domestic market of antibiotics and chemotherapeutic drugs for use in dermatology allowed us to establish that in this segment there are original drugs (30.4 %) and generics (69.6 %), monopreparations (84.1 %) and combined (15.9 %) ones. Drugs of the studied group are represented by various dosage forms, among which soft dosage forms dominate (85.4 %). When studying the corporate structure of this market segment, it was found that 56.6 % of drugs come from abroad from 12 countries of the world and 21 pharmaceutical companies, the leader of which is the United Kingdom (dij = 0.0758). The study of the level of competition showed that the greatest competition is observed among the manufacturers of acyclovir and mupirocin generics (Kvi = 0.89). Calculation of the liquidity ratio, which exceeds 0.5, confirms incomplete availability of these medicines for the population of Ukraine. Conclusions. A marketing study of the domestic market of antibiotics and chemotherapeutic drugs for use in dermatology was conducted. The assortment and corporate structures of this market segment are defined. The level of competitiveness of the pharmaceutical companies is analyzed, and the most successful ones are identified. The liquidity and solvency ratio was calculated, which allowed us to draw conclusions about the availability of these medicines for the population of Ukraine. In the future, in the healthcare system of Ukraine, an important direction should be outlined to improve the system of providing medical care to patients with dermatological diseases.